„Benchmarking“ in der Sozialtherapie: Vergleiche zwischen sozialtherapeutischen Abteilungen für Sexualstraftäter in Bayern - Carl, Lena; Lauchs, Lora; Schmucker, Martin; Lösel, Friedrich (Forensische Psychiatrie, Psychologie, Kriminologie, 2019)
Die Sozialtherapie ist in Deutschland die intensivste Form der Straftäterbehandlung, die insbesondere im Bereich der Sexualdelinquenz Anwendung findet. Noch immer mangelt es an methodisch stichhaltigen Evaluationen, und diese stehen vor erheblichen methodischen und rechtlichen Problemen. Deshalb wurden Studien zur „best practice“ angeregt, die datengestützte Vergleiche zwischen sozialtherapeutischen Einrichtungen gestatten. Dementsprechend verglich die vorliegende Studie sieben sozialtherapeutische Abteilungen für Sexualstraftäter in Bayern hinsichtlich ihrer strukturellen Rahmenbedingungen, der behandelten Straftäter und deren Rückfälligkeit. Bei leichten Unterschieden in den Rahmenbedingungen ergab sich eine starke Varianz in der Klientel, z. B. im Hinblick auf Alter, Art der Sexualdelikte, Substanzmissbrauch, klinische Diagnosen oder Rückfallrisiko im Static-99. Auch die Rückfallraten unterschieden sich zwischen den Einrichtungen, allerdings klärte die Zugehörigkeit zu einer Abteilung weniger als 10 % der Varianz im Rückfall auf. Die Befunde legen nahe, dass die Varianz in den Rückfallraten überwiegend auf Unterschiede in der Klientel zurückzuführen sind und weniger auf Merkmale der Abteilungen und Behandlungsansätze. Schlussfolgerungen für die weitere Forschung und den datengestützten Austausch zwischen den Abteilungen werden erörter
Keywords: Sozialtherapie; Rückfälligkeit; Strafvollzug; Evaluation; Benchmarking; Sexualstraftäter

Die Erfassung der Deliktschwere in Evaluationsstudien zur Straftäterbehandlung: Entwicklung und Anwendung eines strafrahmenorientierten Ansatzes - Lauchs, Lora; Link, Eva; Lösel, Friedrich (Monatsschrift für Kriminologie und Strafrechtsreform, 2020)
Recidivism is the most widely used outcome criterion for measuring treatment success in evaluation studies on offender treatment. Even though a reduction of offense severity would indicate a positive treatment effect, measures of severity are rarely used in research. In this paper, we present an instrument for measuring offense severity based on the statutory sentence lengths in German law. Our severity index was applied to a sample of N = 682 sex offenders and severity codings were carried out on criminal records in the German Federal Central Crime Register. Recidivism severity was defined as the highest severity score for an offense after release from prison. A correlation of r =.59 between the dichotomous recidivism criterion »severe recidivism« (any reconviction with a sentence length of two years or more, custody in a forensic hospital, or preventive detention) and recidivism severity scores support convergent validity. Bivariate analyses revealed significant correlations between offense severity scores and different variables that are associated with violent conduct. This supports the assumption that severity scores based on sentence length adequately reflect the relative severity of different offenses. Furthermore, we found significant correlations with the offenders' age at the time of their release from prison and prior incarceration. This is in accordance with previous findings on correlates of offense severity. Our findings indicate that analyses of recidivism severity, for example the comparison of treated and untreated offenders, should be restricted to recidivists and complement analyses on binary outcome criteria. The application of our severity index was practicable and our results showed its utility in evaluation studies on offender treatment.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Evaluation; harm; offender treatment; offense severity; recidivism criteria; sentence length

On the effectiveness of sexual offender treatment in prisons: A comparison of two different evaluation designs in routine practice - Lösel, Friedrich; Link, Eva; Schmucker, Martin; Bender, Doris; Breuer, Maike Miriam; Carl, Lena; Endres, Johann; Lauchs, Lora (Sexual Abuse-A Journal of Research and Treatment, 2020)
Although there is less continuity of sexual offending in the life course than stereotypes suggest, treatment should lead to a further reduction of reoffending. Contrary to this aim, a recent large British study using propensity score matching (PSM) showed some negative effects of the core sex offender treatment program (SOTP) in prisons. International meta-analyses on the effects of sex offender treatment revealed that there is considerable variety in the results, and methodological aspects and the context play a significant role. Therefore, this study compared different designs in the evaluation of sex offender treatment in German prisons. PSM was compared with an exact matching (EM) by the Static-99 in a sample of 693 sex offenders from Bavarian prisons. Most results were similar for both methods and not significant due to low base rates. There was a treatment effect at p < .05 on general recidivism in the EM and at p = .06 on serious reoffending in the PSM. For sexual recidivism, EM showed a negative trend, whereas PSM suggested the opposite. Overall, the study underlines the need for more replications of evaluations of routine practice, methodological comparisons, sensitive outcome criteria, and differentiated policy informatio
Keywords: sex offender treatment; prison; evaluation design; propensity score matching

Prisoners with Islamist relations. What can we learn from their files - King, Sonja; Endres, Johann; Schwaß, Mariann; Stemmler, Mark; Armborst, Andreas; Lauchs, Lora (International Journal of Developmental Science, 2018)